Computer aided systems theory -- EUROCAST 2019 : 17th International Conference, Las Palmas de Gran Canaria, Spain, February 17-22, 2019, Revised Selected Papers.: 17th International Conference, Las Palmas de Gran Canaria, Spain, February 17-22, 2019, Revised Selected Papers. Part I (2020) - Unknown
No abstract available